The Effect of Leadership and Work Environment on Employee Performance at Bank Mega Syariah in the Tangerang Area - Maulana Yogi Sudia; Nur Asni Gani (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to analyze the influence of leadership and the work environment on employee performance at Bank Mega Syariah’s Tangerang Branch. The dependent variable in this study is employee performance, while the independent variables are leadership and the work environment. This study employs an associative quantitative approach. Primary data were collected through a questionnaire distributed to 36 employees and analyzed using multiple linear regression with the aid of SPSS. The results show that leadership has a positive and significant effect on employee performance, with a calculated t-value of 5.543 > the critical t-value of 2.034 and a p-value < 0.001. Simultaneously, leadership and the work environment also have a positive and significant effect, with a calculated F-value of 58.007 > the critical F-value of 3.28 and a p-value < 0.001. The R-squared value of 0.854 indicates that these two variables account for 85.4% of the variation in employee performance. Thus, effective leadership and a conducive work environment play a crucial role in enhancing productivity and achieving organizational goals.